2020
DOI: 10.3390/ijerph17218043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Smoking, Physical Activity, Screen Time, and Quality of Life among Adolescents

Abstract: Background: Quality of life (QOL) is a crucial part of evaluating health conditions IN adolescents. The purposes of this study were to (1) examine the relationship of QOL and smoking, physical activity (PA) and screen time (ST) among Chinese adolescents, (2) explore the relationship between PA-ST combination and QOL of adolescents, and (3) investigate the dose-response relationship between PA-ST and QOL. Methods: This study randomly selected 12,900 adolescents (11–18 years) from 13 administrative regions in Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Finally, in the models adjusted for the covariates, our results showed significance for physical activity and screen time in the combination of the three behaviors in the total sample and in physical activity for males. In this sense, our findings are consistent with those found in previous studies [ 47 , 48 , 49 ] where the amount and intensity of physical activity are related to a better quality of life. Likewise, the fact that physical activity was only significant in predicting quality of life in boys could be due to leisure opportunities, differences in social and cultural roles, and psychological attributes [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, in the models adjusted for the covariates, our results showed significance for physical activity and screen time in the combination of the three behaviors in the total sample and in physical activity for males. In this sense, our findings are consistent with those found in previous studies [ 47 , 48 , 49 ] where the amount and intensity of physical activity are related to a better quality of life. Likewise, the fact that physical activity was only significant in predicting quality of life in boys could be due to leisure opportunities, differences in social and cultural roles, and psychological attributes [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Educational scale value ranged from 3 to 18 while occupational scale value ranged from 5 to 30. The total SES index ranged from 8 to 48 and was categorized as high (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), moderate (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and low (8-21) (43). The validity and reliability of this instrument were endorsed by Cirino et al (42).…”
Section: Demographic and Other Characteristicsmentioning
confidence: 99%
“…Research conducted by 25 supports the above statement, that there are some young women in China's Shandong Province who smoke, either with the classi cation of "ever smoked" or "frequently smoked" in 30 last day. Study conducted in the America by 26 is in line with what was found from this study, namely that the number of female smokers is dominated by the 26-44 year age group.…”
Section: Discussionmentioning
confidence: 73%